2021
DOI: 10.1159/000521230
|View full text |Cite
|
Sign up to set email alerts
|

History of Suicide Attempts and COVID-19 Infection in Veterans with Schizophrenia or Schizoaffective Disorder: Moderating Effects of Age and Body Mass Index

Abstract: Introduction: Relative to the general population, patients with schizophrenia or schizoaffective disorder have higher rates of suicide attempts and mortality from COVID-19 infection. Therefore, determining whether a history of suicide attempt is associated with COVID-19 in patients with schizophrenia or schizoaffective disorder has implications for COVID-19 vulnerability stratification in this patient population. Methods: We carried out cross-sectional analyses of electronic health records (EHR) of veterans w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In this study, we found that 23.5% of SZ patients had suicidal ideation, which is consistent with the results of previous studies [ 25 , 36 38 ].Moreover, we found that young SZ patients had higher risk of suicidality than middle-aged and elderly SZ patients, which is consistent with the previous studies [ 2 , 39 ].Meanwhile, young age was a risk factor for suicidal ideation in middle-aged and elderly SZ patients. A positive effect of age on mental health-related quality of life (HRQOL) has been found in the previous study [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that 23.5% of SZ patients had suicidal ideation, which is consistent with the results of previous studies [ 25 , 36 38 ].Moreover, we found that young SZ patients had higher risk of suicidality than middle-aged and elderly SZ patients, which is consistent with the previous studies [ 2 , 39 ].Meanwhile, young age was a risk factor for suicidal ideation in middle-aged and elderly SZ patients. A positive effect of age on mental health-related quality of life (HRQOL) has been found in the previous study [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, none of the studies reviewed within the scope of this meta-analysis addressed the suicidal behavior in psychotic disorders. In a study in which the relationship between suicide attempts and being infected with COVID-19 in veterans with schizophrenia and schizoaffective disorder was investigated, the rate of suicide attempts during the pandemic was reported as 2.7% ( Okusaga et al, 2021 ). In comparison, in this study, the rates of patients with suicidal ideation during the pandemic period was found as 40.7%, and patients who attempted suicide during the pandemic period were found as 11.3%, and the rates were higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a differential association between BMI and fronto-limbic white matter microstructure was found among patients with first-episode schizophrenia spectrum disorders [ 24 ]. Furthermore, BMI and age had the moderating effects of an association between a history of suicidal attempts and COVID-19 infection among patients with schizophrenia or schizoaffective disorder [ 25 ]. Therefore, BMI and other sociodemographic and clinical data were included as one of the variable profiles for the substantial prediction model.…”
Section: Methodsmentioning
confidence: 99%